The lncRNA Plscr4 Controls Cardiac Hypertrophy by Regulating miR-214 - Lifang Lv; Tianyu Li; Xuelian Li; Chaoqian Xu; Qiushuang Liu; Hua Jiang; Yingnan Li; Yingqi Liu; He Yan; Qihe Huang; Yuhong Zhou; Mingyu Zhang; et al. (Elsevier, 2018)
Cardiac hypertrophy accompanied by maladaptive cardiac remodeling is the uppermost risk factor for the development of heart failure. Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) have various biological functions, and their vital role in the regulation of cardiac hypertrophy still needs to be explored. In this study, we demonstrated that lncRNA Plscr4 was upregulated in hypertrophic mice hearts and in angiotensin II (Ang II)-treated cardiomyocytes. Next, we observed that overexpression of Plscr4 attenuated Ang II-induced cardiomyocyte hypertrophy. Conversely, the inhibition of Plscr4 gave rise to cardiomyocyte hypertrophy. Furthermore, overexpression of Plscr4 attenuated TAC (transverse aortic constriction)-induced cardiac hypertrophy. Finally, we demonstrated that Plscr4 acted as an endogenous sponge of miR-214 and forced expression of Plscr4 downregulated miR-214 expression to promote Mfn2 and attenuate hypertrophy. In contrast, knockdown of Plscr4 upregulated miR-214 to induce cardiomyocyte hypertrophy. Additionally, luciferase assay showed that miR-214 was the direct target of Plscr4, and overexpression of miR-214 counteracted the anti-hypertrophy effect of Plscr4. Collectively, these findings identify Plscr4 as a negative regulator of cardiac hypertrophy in vivo and in vitro due to its regulation of the miR-214-Mfn2 axis, suggesting that Plscr4 might act as a therapeutic target for the treatment of cardiac hypertrophy and heart failure.